1991
DOI: 10.1007/bf00314987
|View full text |Cite
|
Sign up to set email alerts
|

In vitro forecasting of drugs which may interfere with the biotransformation of midazolam

Abstract: The biotransformation of midazolam is mediated by a cytochrome P-450 isozyme (P-450 IIIA) whose activity is highly variable. The kinetics of the 1'- and 4-hydroxylation of midazolam, the major routes of midazolam oxidation, by human liver microsomes have been examined to characterize further the cytochrome isozyme(s) catalysing these reactions, and to screen for drugs that might interfere with them. In hepatic microsomal preparation from two kidney donors (extensive and poor metabolisers of debrisoquine) KM va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
41
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 29 publications
10
41
0
2
Order By: Relevance
“…K m values for midazolam 1Ј-hydroxylase were 2.27 Ϯ 0.18, 0.622 Ϯ 0.025, and 1.53 Ϯ 0.09 M in HLM, rCYP3A4, and rCYP3A5, respectively (Table 7; Fig. 2), consistent with previously reported values of 2.4 to 12 M for liver microsomes (Gascon and Dayer, 1991;Sharer et al, 1995;Ghosal et al, 1996; Transon et al, 1996;Von Moltke et al, 1996b;Maenpaa et al, 1998;Wandel et al, 1998;Wang et al, 1999;Martinez et al, 2000;Warrington et al, 2000;Yin et al, 2000;Hamaoka et al, 2001;Andrews et al, 2002;Li et al, 2003) (Fig. 4), 1.0 to 8.9 M for rCYP3A4 (Ghosal et al, 1996;Gibbs et al, 1999;Eiselt et al, 2001;Khan et al, 2002;Obach and Reed-Hagen, 2002;Williams et al, 2002;Yamaori et al, 2003), and 4.1 to 14 M for rCYP3A5 (Gibbs et al, 1999;Williams et al, 2002;Yamaori et al, 2003).…”
Section: Validated Assays For Human Cytochrome P450 Enzymessupporting
confidence: 80%
“…K m values for midazolam 1Ј-hydroxylase were 2.27 Ϯ 0.18, 0.622 Ϯ 0.025, and 1.53 Ϯ 0.09 M in HLM, rCYP3A4, and rCYP3A5, respectively (Table 7; Fig. 2), consistent with previously reported values of 2.4 to 12 M for liver microsomes (Gascon and Dayer, 1991;Sharer et al, 1995;Ghosal et al, 1996; Transon et al, 1996;Von Moltke et al, 1996b;Maenpaa et al, 1998;Wandel et al, 1998;Wang et al, 1999;Martinez et al, 2000;Warrington et al, 2000;Yin et al, 2000;Hamaoka et al, 2001;Andrews et al, 2002;Li et al, 2003) (Fig. 4), 1.0 to 8.9 M for rCYP3A4 (Ghosal et al, 1996;Gibbs et al, 1999;Eiselt et al, 2001;Khan et al, 2002;Obach and Reed-Hagen, 2002;Williams et al, 2002;Yamaori et al, 2003), and 4.1 to 14 M for rCYP3A5 (Gibbs et al, 1999;Williams et al, 2002;Yamaori et al, 2003).…”
Section: Validated Assays For Human Cytochrome P450 Enzymessupporting
confidence: 80%
“…Ketoconazole is an inhibitor of several P450s, but is a particular potent inhibitor of CYP3A isoforms with an apparent Ki value of 0.1 gM in human liver microsomes [46]. We found that ketoconazole was a weak inhibitor of all three oxidative pathways of theophylline metabolism, suggesting that CYP3A is not important for the formation of 13DMU.…”
Section: Discussionmentioning
confidence: 67%
“…Gascon and Dayer (1991) described the kinetics of midazolam with HLMs and also found that formation of 1Ј-hydroxymidazolam and 4Ј-hydroxymidazolam was linear up to 15 min only with HLMs. Product inhibition (1Ј-hydroxymidazolam and/or 4Ј-hydroxymidazolam formation) after 10 min could account for the nonlinearity.…”
Section: Discussionmentioning
confidence: 97%